2613. The Epidemiology of Respiratory Syncytial Virus (RSV) in People with Immune Dysfunction Seen at a Tertiary Hospital Between 2010 and 2017 - Li, Qiuju (Open Forum Infect Dis, 2019)
BACKGROUND: Persons with a compromised immune system are at increased risk of complications related to respiratory syncytial virus (RSV) but the risks are not well defined. We aimed to investigate the prevalence of RSV infection, associated risk factors and complications in a large population of people with immune dysfunction. METHODS: Persons with immune dysfunction, first seen at Copenhagen University Hospital, Rigshospitalet, between January 1, 2010 and February 21, 2017, aged ≥18 were included. RSV testing and positivity (positive PCR or antigen test) was determined through the Danish Microbiology Database. Generalized estimating equations logistic regression was used to investigate the risk factors for RSV positivity; Cox regression was used to assess the impact of RSV positivity (time-updated) on mortality in the first 12 months after first visit. RESULTS: The study included 42,567 persons, of which 3,356 (7.9%, 95% CI 7.6%-8.1%) were tested for RSV at least once during follow-up, with 2,374 (71%) tested in the first 12 months. Stem cell transplant (HSCT) and solid-organ transplant (SOT) recipients had the highest proportion of persons tested for RSV (66.0%, 95% CI 62.9%–69.1% and 31.6%, 95% CI 29.0%–34.2%, respectively). Of those tested, 256 (7.6%, 95% CI 6.7%–8.5%) had ≥1 positive RSV test (figure). After adjustment, HSCT and SOT recipients, as well as other hematologic and rheumatologic patient groups were more likely to have a positive RSV test compared with persons seen in the infectious disease department. Fifty-seven RSV-related complications were identified in 53/256 (20.7%, 95% CI 15.7%-25.7%) persons positive for RSV (table), of which 24 (45.3%) were HSCT recipients and 18 (34.0%) were other hematologic patients. In the 12 months after first department visit, 9,451 (22%) patients died; persons with RSV had an increased risk of short-term mortality (aHR 1.77, 95% CI 1.19–2.64), adjusting for sex, age, patient group and flu positivity. CONCLUSION: Patients with a hematological or rheumatological condition and SOT recipients had the highest odds of contracting RSV, with hematological patients in particular at an excess risk of RSV-related complications. RSV was associated with an increased risk of death in the first 12 months of patient follow-up. [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.